Urgensi dan Kontribusi Teknologi Informasi dalam Memverifikasi Awal Waktu Shubuh dan Ketinggian Hilal Penentu Awal Bulan Hijriah - Qulub, Siti Tatmainul; Munif, Ahmad (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2023)
The sun's altitude of -20o as a reference for determining the beginning of dawn time used by the Ministry of Religious Affairs is again questionable. Meanwhile, in terms of hilal height as one of the criteria for determining the beginning of the Hijri month, the Ministry of Religion has also undergone adjustments and changes in 2022. The new criteria of MABIMS mention criteria in the form of a hilal height of 3 o  and an elongation angle of 6.4o. This research answers two formulations of problems, first, how the urgency of information technology in determining the criteria for the beginning of dawn and the criteria for determining the beginning of the qamariyah month in Indonesia. Second, the extent of the contribution of information technology in determining the criteria for dawn and the criteria for determining the beginning of the qamariyah month in Indonesia. Analytical descriptive methods with fiqh and scientific approaches are used to answer both formulations of the problem. The study produced two findings. First, according to Islamic law, the presence of digital-based information technology is considered legal to be used and utilized to provide certainty and trust in Islamic legal products. Secondly, technology has made a major contribution in verifying dawn criteria and establishing new criteria of MABIMS.